1982
DOI: 10.1295/polymj.14.347
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Benzene–Cyclohexane Azeotropic Mixture through Polymeric Membranes with Microphase Separated Structures

Abstract: 2-Hydroxyethyl methacrylate (HEMA) (branch)-methyl acrylate (MA) (backbone) comb-type graft copolymers were synthesized by grafting an amino-semitelechelic oligo (HEMA) to a methacrylate (GMA) random copolymer. From electron microscope observation, it was found that these graft polymeric membranes had microphase separated structures. Pervaporation of a benzene-cyclohexane mixture through these membranes was carried out in order to study the effect of microphase separated structures on selective permeability. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…6 The composition and flux of the permeate were determined by gas chromatography (Shimadzu GC-3BT Type). !-Propanol served as the internal standard for the determination of the permeated solvents.…”
Section: Pervaporation Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…6 The composition and flux of the permeate were determined by gas chromatography (Shimadzu GC-3BT Type). !-Propanol served as the internal standard for the determination of the permeated solvents.…”
Section: Pervaporation Experimentsmentioning
confidence: 99%
“…The pervaporation rate and separation factor were defined in a previous paper as, P=w·8/a·t where w, 8, a and t denote the permeate flux, the membrane thickness, the membrane area and time, respectively. 6 Pervaporation using a liquid-polymer hybrid membrane was carried out as follows. After carbon tetrachloride as the liquid membrane was put on the HEA-AN graft copolymer membrane, ethanolwater as a feed solvent was injected into the liquid membrane and then pervaporation was started.…”
Section: Pervaporation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In separation of the benzene-cyclohexane mixtures, Shinohara et al has reported that 2-hydroxyethyl methacrylate-methyl acrylate graft copolymer membranes 1 and 2-hydroxy-3-(diehtylamino)propyl methacrylate-styrene copolymer membranes with cyanuric choloride 2 exhibited excellent benzene permselectivity. In order to depress the swelling of polymer membranes caused by organic solvent, the hydrophilic polymers are used.…”
Section: Introductionmentioning
confidence: 99%